ANALISIS KARAKTERISTIK FISIK DAN NON FISIK NEGARA INDONESIA DAN BRUNEI DARUSSALAM - Saragih, Luksiade (Program Studi Pendidikan Geografi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Samudra, 2024)
This study examines two developing countries in Southeast Asia, namely Indonesia and Brunei Darussalam, which are guided by the same latitude position. The purpose of this study is to determine the physical and non-physical characteristics of Indonesia and Brunei Darussalam, the potential of each country, the strengths and weaknesses of both countries, and the challenges in each country. This study is a study using a literature study method that focuses on the results of writing related to the topic or writing variables. The results of the study show that the strategic geographical location makes Indonesia a trade route. The tropical climate makes this region fertile, there are many mountain paths so that the Indonesian region becomes a suitable area for various plants and animals. Brunei Darussalam can be categorized as a developed country because this country still relies on and depends its country's economy on the primary sector in the form of oil and natural gas mining. Brunei Darussalam and Indonesia both have advantages in abundant natural resources, but the economic systems of both countries are less advanced.